Chiral BrOnsted Acid-Catalyzed Friedel-Crafts Reaction of Indoles - S. Bhadury, Pinaki; Pang, Jun (Current Organic Chemistry, 2014)
The indole network has been identified as an important pharmacophore of several natural products and synthetically prepared molecules. Asymmetric organocatalytic Friedel-Crafts alkylations of electron rich indoles are of enormous significance for the synthesis of many bioactive compounds, natural products and anti-cancer drugs. Chiral BrOnsted acid-catalyzed Friedel-Crafts-type reactions of indole and its derivatives with various carbon-centered electrophiles e.g. electron deficient olefins, carbonyls, imines and some substituted methanamines and carbinols have been employed to prepare optically active indole derivatives. These reactions, their stereochemical outcome and probable modes of activation of the substrates by suitably substituted axially dissymmetric BINOL-derived chiral BrOnsted acid catalysts are discussed in this review.
Keywords: enantioselectivity